Affecting Factors of the Accuracy of Receipt of Covid-19 Vaccination in South Buton Regency - Wahyuddin, Wahyuddin; Syaputri, Iis S.A; Taswin, Taswin; Amirudiin, Eky E. (Community Research of Epidemiology (CORE), 2022)
Accuracy in the implementation of the Covid-19 Vaccination Receipt is an action taken by the government to the community in an effort to reduce the number of Covid-19 cases. The purpose of this study was to determine the factors related to the accuracy of the implementation of the community receiving the Covid-19 vaccination in the working area of the UPTD Puskesmas Batauga, South Buton Regency. The research design used is quantitative analytic by using a cross sectional study design. Collecting data using a research instrument in the form of a questionnaire. Based on the results of the chi-square test with a limit of significance (=0.05). The population in this study are people who are in the working area of UPTD Puskesmas Batauga, South Buton Regency, especially people aged 12 years and over. Determination of the estimated number of samples using the Lemeshow formula with a sample size of 371 people. The results showed that there was a significant relationship between participation p value = 0.000 (<0.05)), Motivation p value = 0.000 (<0.05)), and there is no relationship between sources of information media p value= 0.062 (>0.05)) with the accuracy of the implementation of the community receiving the Covid-19 vaccination in the working area of the UPTD Puskesmas Batauga, South Buton Regency. The conclusion of this study is that the participation, motivation of information media sources have an influence on the accuracy of the implementation of the community receiving the covid-19 vaccination in the working area of the UPTD Puskesmas Batauga, South Buton Regency. Therefore, massive education is needed from health workers with accurate and relevant information to increase public literacy regarding the covid vaccine